Gene Expression as a Biomarker for Predicting Primary Doxorubicin Resistance in Breast Cancer. - Demir, S; Müslümanoğlu, M H; Müslümanoğlu, M; Başaran, S; Çalay, Z Z; Aydıner, A; Vogt, U; Çakır, T; Kadıoğlu, H; Artan, S (My University, 2019)
Doxorubicin is one of the most commonly used chemotherapeutic agents for adjuvant chemotherapy of breast cancer. In the studies focused on finding biomarkers to predict the response of the patients and tumors to the drugs used, the Twist transcription factor has been suggested as a candidate biomarker for predicting chemo-resistance of breast tumors. In this study, we aimed to investigate the relationship between TWIST transcription factor expression and the effectiveness of doxorubicin treatment on directly taken primary tumor samples from chemotherapy-naive breast cancer patients. Twenty-six primary breast tumor samples taken from 26 different breast cancer patients were included in this study. Adenosine triphosphate tumor chemo-sensitivity assay (ATP-TCA) has been used to determine tumor response to doxorubicin and real-time reverse-transcription polymerase chain reaction (RT-PCR) was used for analyzing the gene expression of tumors. There was a significant difference in gene expression between responder and non responder tumors ( <0.05). The gene expression of the drug-resistant group was higher than the responsive group. This difference was not dependent on the histopathological features of tumors. In conclusion, compatible with earlier studies that have been performed with cell lines, the current study supports the role of higher gene expression as a biomarker for predicting the response of breast tumors to chemo-therapeutic agent doxorubicin.
Keywords: Biomarker; Breast cancer; Chemotherapy; Expression; TWIST1 gene